Development of Google Sites-Based Interactive Learning Media on Historical Relics Material for Fourth Grade Elementary School Students - Suyanti Suyanti; Dian Nur Antika Eky Hastuti; Eka Nofri Ariyanto; Silvia Pritama (Universitas Negeri Padang, 2026)
This study aimed to develop interactive web-based learning media on historical relics material for fourth-grade elementary school students and to examine the feasibility and practicality of the developed media. The study employed a Research and Development (R&D) approach using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The validators involved in this study consisted of two subject matter experts, one language expert, and one media expert. The practicality test subjects included one fourth-grade teacher and eight fourth-grade students of SDN Banjarejo. The subjects were selected using purposive sampling techniques based on the needs of the study. Data were collected through observation sheets and questionnaires, while data analysis was conducted using descriptive percentage analysis based on a Likert scale. The developed learning media integrated Google Sites with Canva, Wordwall, and YouTube to support interactive learning activities. The validation results showed an average feasibility score of 95.67%, categorized as highly feasible, while the practicality test results from the teacher and students obtained an average score of 95.47%, categorized as highly practical.The developed learning media received positive responses from teachers and students and was considered highly practical to support the learning process